Fatty acid binding protein 7 as a marker of glioma stem cells. (26th November 2013) - Morihiro, Yusuke; Yasumoto, Yuki; Vaidyan, Linda Koshy; Sadahiro, Hirokazu; Uchida, Tomoyuki; Inamura, Akinori; Sharifi, Kazem; Ideguchi, Makoto; Nomura, Sadahiro; Tokuda, Nobuko; Kashiwabara, Shoji; Ishii, Aya; et al.
<x xml:space="preserve">Abstract</x> Glioblastomas are the most aggressive brain tumors. Glioblastoma stem cells (GSCs) are thought to be responsible for the recurrence, chemoresistance, and poor prognosis of glioblastoma. Fatty acid binding protein 7 (FABP7), which is a cellular chaperone for a variety of omega‐3 fatty acids, is a known marker for neural stem cells. In this study, using a newly developed anti‐FABP7 antibody and patient‐derived GSC lines, we evaluated the expression of FABP7 in GSCs. Using immunocytochemistry, Western blotting, and qPCR analyses, FABP7 was found to be highly enriched in GSCs and its localization was found in cytosol and nuclei. FABP7 expression was significantly downregulated in differentiated GSCs induced by the addition of serum. In the glioma surgical specimens, FABP7 was highly expressed in the majority of glioblastoma. Double immunostaining for FABP7 and Sox2 showed that FABP7+Sox2+ tumor cells were significantly increased in glioblastoma (grade IV) compared with diffuse astrocytoma (grade II) and anaplastic astrocytoma (grade III). Our data introduces FABP7 as a marker for GSCs and further highlights its possible significance for glioma diagnosis and treatment.